Anxiety and Social Withdrawal Among Children: Associations with Emotion Awareness and Emotion Regulation Strategy Use at the Intra- and Interpersonal Levels - (:unkn) unknown (My University, 2021)
Anxiety and social withdrawal are two frequently experienced internalizing conditions among children. These early-onset challenges are associated with numerous maladaptive outcomes in the academic, social, and psychological domains (Levitt & Merrill, 2009; Long, 2018; Sanchez et al., 2018; Shernoff et al., 2017). While identifying anxious and socially withdrawn children in the classroom is difficult as symptoms generally occur internally, distinguishing between the conditions is perhaps more challenging as the two are closely associated, oftentimes overlapping constructs (Barzeva et al., 2019; Rubin et al., 2009). Particularly, it is unclear whether anxiety and social withdrawal are similarly or differently associated with key emotion regulation-related processes. While ineffective regulation of emotions is consistently linked to the development and maintenance of internalizing conditions in children (Bender et al., 2012; Kranzler et al., 2016; Penza-Clyve & Zeman, 2002; Sendzik et al., 2017), the association to key components is much less understood especially at the interpersonal level. To address this challenge, the researcher examined anxiety and social withdrawal through the lens of emotion awareness and emotion regulation strategy use at the intra- and interpersonal levels. Study participants were 398 fourth- and fifth-grade children (M age = 10.3) and their classroom teachers. Self-report was used to assess anxiety, intra- and interpersonal emotion awareness, as well as the use of intrapersonal adaptive and maladaptive strategies. Teacher-report was used to measure social withdrawal while peer-report was used to assess classmates’ use of interpersonal supportive and unsupportive strategies. In general, anxiety related to intrapersonal emotion regulation-related processes while social withdrawal related to interpersonal processes. More specifically, anxiety significantly associated with poorer intrapersonal emotion awareness and greater use of adaptive strategies to regulate one's own emotions. Comparatively, social withdrawal significantly associated with poorer awareness of others’ emotions and less use of interpersonal supportive and unsupportive emotion regulation strategies. The researcher’s findings indicate anxiety and social withdrawal can be distinguished from each other regarding their associations with intra- verses interpersonal emotion awareness and emotion regulation strategy use. The information may assist teachers, school psychologists, and other school personnel in more timely and accurate identification and treatment (e.g., emotion regulation skill building) for children experiencing these challenges in the classroom setting.
Keywords: Anxiety; Children; Emotion awareness; Emotion regulation; Social withdrawal; Strategy use